Identification of a triplet pair intermediate in singlet exciton fission in solution. - Stern, H; Musser, A; Gelinas, S; Parkinson, P; Herz, L; Bruzek, M; Anthony, J; Friend, R; Walker, B (National Academy of Sciences, 2015)
Singlet exciton fission is the spin-conserving transformation of one spin-singlet exciton into two spin-triplet excitons. This exciton multiplication mechanism offers an attractive route to solar cells that circumvent the single-junction Shockley-Queisser limit. Most theoretical descriptions of singlet fission invoke an intermediate state of a pair of spin-triplet excitons coupled into an overall spin-singlet configuration, but such a state has never been optically observed. In solution, we show that the dynamics of fission are diffusion limited and enable the isolation of an intermediate species. In concentrated solutions of bis(triisopropylsilylethynyl)[TIPS]--tetracene we find rapid (<100 ps) formation of excimers and a slower (∼ 10 ns) break up of the excimer to two triplet exciton-bearing free molecules. These excimers are spectroscopically distinct from singlet and triplet excitons, yet possess both singlet and triplet characteristics, enabling identification as a triplet pair state. We find that this triplet pair state is significantly stabilized relative to free triplet excitons, and that it plays a critical role in the efficient endothermic singlet fission process.